Effect of anxiety and depression on self-reported adverse reactions to COVID-19 vaccine: a cross-sectional study in Shanghai, China - Zhitong Zhou; Junwei Shen; Miaomiao Zhao; Xiaoying Zhang; Tao Wang; Jue Li; Xudong Zhao (BMC, 2023)
Abstract Background The association of anxiety and depression with adverse reactions after receipt of coronavirus disease 2019 (COVID-19) vaccine is not clear among the general population. This study aims to evaluate the effect of anxiety and depression on self-reported adverse reactions to COVID-19 vaccine. Methods The cross-sectional study was conducted during April-July 2021. Participants completing the two doses of vaccine were included in this study. Sociodemographic information, anxiety and depression levels and adverse reactions after the first dose of vaccine for all participants were collected. The anxiety and depression levels were assessed by the Seven-item Generalized Anxiety Disorder Scale and the Nine-item Patient Health Questionnaire Scale, respectively. The multivariate logistic regression analysis was used to examine the association between anxiety and depression and adverse reactions. Results A total of 2161 participants were enrolled in this study. The prevalence of anxiety and depression was 13% (95% confidence interval (CI), 11.3-14.2%) and 15% (95%CI, 13.6-16.7%), respectively. Of the 2161 participants, 1607 (74%; 95% CI, 73-76%) reported at least one adverse reaction after the first dose of the vaccine. Pain at the injection site (55%) and fatigue and headache (53% and 18%, respectively) were the most commonly reported local and systemic adverse reactions, respectively. Participants with anxiety or depression or both were more likely to report local and systemic adverse reactions (P < 0.05). Conclusion The results suggest that anxiety and depression increase the risk of self-reported adverse reactions to COVID-19 vaccine. Consequently, appropriate psychological interventions before vaccination will help to reduce or alleviate symptoms of vaccination.